Uso de agregado reciclado miúdo como agente de cura interna em compósitos cimentícios - Paulo Henrique Vaz da Silva (2023)
The construction industry is responsible for generating a significant amount of solid waste, which has a high potential to be used as recycled aggregates in the production of concrete and mortar. Recycled aggregates differ from natural ones due to the presence of adhered mortar on the grains, which increases porosity and water absorption. This additional water absorption and subsequent release can modify the hydration reactions of the cementitious matrix. Therefore, the objective of this study is to evaluate the use of fine recycled aggregate as an internal curing agent in cementitious composites. Mortars were produced with volumetric substitution of natural sand by recycled aggregate at rates of 20% and 40%, with CPV-ARI and CPIII-RS cements, and w/c ratios of 0,42, 0,44, and 0,45. In the fresh state, the physical properties of the mortars were evaluated, while in the hardened state, both physical and mechanical properties, as well as durability, were evaluated up to 91 days. The results indicated that, although mortars with recycled aggregate were more absorbent and porous, no significant difference was observed in the flexural and compressive strengths of samples with the same w/c ratio. However, there was a reduction in mechanical strength only for mortars with 40% substitution of conventional aggregate, using CP III-RS and additional water. No change in the hydration heat peak was observed in the first hours; however, an anticipation of its occurrence was observed. An increase in autogenous shrinkage was not observed with the incorporation of recycled aggregate, both for mortars produced with CPIII-RS and CPV-ARI. Drying shrinkage also did not show significant differences between the samples. However, for autogenous shrinkage, the recycled aggregate acted differently between the two types of cement, depending on the control of water availability for hydration reactions. For CPIII-RS cement, there was an increase in autogenous shrinkage, indicating an increase in the hydration rate of this composite cement. For CPV-ARI, a reduction in autogenous shrinkage was observed, reducing the effects of the rapid reaction of this cement. Therefore, the use of fine recycled aggregate as an internal curing agent result in the alteration of the hydration mechanisms of the cementitious matrix and allows the maintenance of mechanical and durability properties equivalent to conventional mortars.